Information services using a scientific approach to prevent the tendency of student physical bullying - Suhaili, Neviyarni; Netrawati, Netrawati; Syarifuddin, Syarifuddin (Universitas Negeri Padang, 2020)
The tendency of student physical bullying must be prevented because it can negatively impact physical and psychological aspects for the perpetrator, the audience, and the victim. One way that can be done to prevent this tendency is by providing information services using a scientific approach. This study aimed to test the effectiveness of information services using a scientific approach to prevent student physical bullying tendency. This study was a quantitative research with the actual experimental design, the randomized pretest-posttest control group design. The research sample consisted of 30 students for the experimental group and 30 students for the control group. The data were analyzed by using the non-parametric statistics using the Kolmogorov Smirnov 2 independent sample analysis technique. The study results proved that information services using a scientific approach are effective in preventing the tendency of student physical bullying.